Treatment Patterns among Patients with Atopic Dermatitis in Secondary Care: A National, Observational, Non-interventional, Retrospective Study in Sweden - Emma K. Johansson; Andreas Brenneche; Dennis Trangbaek; M. Natalia Stelmaszuk; Jonatan Freilich; Chris D. Anderson (Acta Dermato-Venereologica, 2022)
This non-interventional, observational, longitudinal study describes treatment patterns of atopic dermatitis (AD) in Sweden. Data from 3 Swedish registries were merged, and included patients who received an AD diagnosis (during the period 1997 to 2019) and had AD treatment prescribed (during the period 2006 to 2020). Treatment persistence, treatment sequencing, time-to-event analysis, and 12-month prevalence were analysed. Overall, data for 99,885 patients with AD were included, of whom 4,086 (4.1%) received systemic treatments. Median persistence rates were 12.6 (95% CI 11.9, 13.4) months for methotrexate, 10.8 (9.1, 13.0) months for azathioprine, 5.6 (3.8, 6.2) months for mycophenolate, 5.1 (4.4, 5.7) months for alitretinoin and 3.4 (3.2, 3.7) months for cyclosporine. Median (Q1, Q3) time from first secondary care visit for AD to first systemic treatment was 5.8 (2.2, 11.0) years overall and 4.4 (1.3, 9.1) years in the Stockholm region. Methotrexate was a prominent first- and second-line treatment used during the period 2006 to 2020. Dupilumab was introduced during the study period and was increasingly used as first- or second-line therapy over time. The 12-month prevalence of AD generally remained steady, with a gradual increase observed over time for the overall population. A steep increase was observed in Stockholm from 2011. This study shows that a small proportion of patients with AD are offered systemic treatments in Sweden, with long periods in secondary care prior to systemic treatments and low persistence on systemic treatments. Regional differences highlight a need for national treatment guidelines.